Papua Conflict: An Article Review from the Best Conflict Resolution Method - Merina, Bresca (Journal of Education on Social Science (JESS), 2024)
This article is aimed to review conflict resolution process of Armed Criminal Group in Papua (KKB). This study is a scientific-article review using comparison technique, which compares horse trading method, counter-insurgency (COIN) model, and Military Operations Other Than War (OMSP) to later review the best method in conflict resolution and renew or develop it. This study starts from revealing the background of Armed Criminal Group (KKB) happening in Papua, and then discussing conflict resolution process referring to the separatist movement development from KKB using horse trading method, which is proven effective to resolve this conflict if it is supported by the trust between two parties to have a dialogue where both parties are allowed to deliver their purposes openly. It is different from the application of McCormick’s COIN strategy model which narrowly fails in resolving Papua conflict, and even is possible to create a chance of the new dynamics’ existence in its international dimension, so it is needed to have a new interpretation towards COIN model in Papua, which is by giving solution to conflict-root elimination instead of total elimination by military. Meanwhile, applying Military Operations Other Than War approach (OMSP) is mandatory which is done by every country in order to tackle separatism movements. By those three models mentioned earlier, several strategic steps are formulated later in conflict resolution of Armed Criminal Group (KKB) in Papua.